2018
DOI: 10.1186/s12917-018-1573-2
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal groove dysfunction: a cause of ruminal bloat in newborn calves

Abstract: BackgroundEsophageal groove dysfunction is one of the major causes of ruminal bloat. This condition is fatal in new born calves if it is not treated early. In healthy, suckling calves, milk should bypass the forestomach (rumen and reticulum) and enter into the abomasum where enzymatic digestion of milk proteins takes place. However, failure of the esophageal groove allows milk to enter into the forestomach, which results in the production of excess gases by microbial fermentation. Consequently, this increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
(10 reference statements)
0
7
0
1
Order By: Relevance
“…Results from previous studies also indicated that the use of open-pails to milk-feed of dairy calves increase the risk of harming their welfare, since under such conditions calves are not able to express proper suckling behaviour, resulting in motivational and physiological disturbances, characterized by the expression of crosssuckling (abnormal) behaviour (de Passillé, 2001) and when the oesophageal groove close incompletely (Martín-Alonso et al, 2018). Thus, it is likely that using nipple-pails after the GPH adoption has contributed to reduce calves frustration (de Passillé, 2001), and to improve milk digestion, either by preventing milk from being fermented in the rumen (Kaba, Abera, & Kass, 2018) or by enhancing the production of digestive Acta Scientiarum. Animal Sciences, v. 43, e53327, 2021 enzymes (stimulated by suckling), which reduce the risk of osmotic diarrhoea caused by milk fermentation in the intestines (Quigley lll, Drewry, Murray, & Ivey, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Results from previous studies also indicated that the use of open-pails to milk-feed of dairy calves increase the risk of harming their welfare, since under such conditions calves are not able to express proper suckling behaviour, resulting in motivational and physiological disturbances, characterized by the expression of crosssuckling (abnormal) behaviour (de Passillé, 2001) and when the oesophageal groove close incompletely (Martín-Alonso et al, 2018). Thus, it is likely that using nipple-pails after the GPH adoption has contributed to reduce calves frustration (de Passillé, 2001), and to improve milk digestion, either by preventing milk from being fermented in the rumen (Kaba, Abera, & Kass, 2018) or by enhancing the production of digestive Acta Scientiarum. Animal Sciences, v. 43, e53327, 2021 enzymes (stimulated by suckling), which reduce the risk of osmotic diarrhoea caused by milk fermentation in the intestines (Quigley lll, Drewry, Murray, & Ivey, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…However, the abrupt weaning of calves unto hay and concentrates should curb the calves' condition that fails to respond to these measures (Breukink et al, 1988). Severe chronic cases of associated bloat might require rumenostomy (Kaba et al, 2018). Ruminal drinking is a recognizable and preventable condition on cattle farms with early diagnosis and treatment or appropriate management practices.…”
Section: Discussionmentioning
confidence: 99%
“…Oesophageal groove dysfunction in calves entirely on the milk diet might lead to the spillage of the ingested milk into the reticulo-rumen instead of directly into the abomasum resulting in a condition known as ruminal drinking (RD) or reticulo-rumen milk accumulation (Dirr and Dirksen, 1989;Adetunji et al, 2016). The condition may predispose affected calves to fermentative ruminal acidosis (Gentile et al, 2004), including rumen mucosal ulceration and necrosis, maldigestion, and recurrent tympany or bloat (Gentile, 2004;Adetunji et al, 2016;Kaba et al, 2018). Despite reports of RD cases in calves, there is a paucity of information on its exact pathogenesis (Breukink et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Esophagus obstructions (external particles cloths and fruit material, etc. ), cysts, blisters, tumors, thoracic or cervical enlargement, reticular dysfunction, and hypocalcemia are major conditions affecting gas belching ( 100 102 ). Frothy bloat is the result of feed ingestion, which continuously produces froth that cannot be easily expelled from the stomach.…”
Section: Metabolic Disorders In Ruminantsmentioning
confidence: 99%